Impact of Body Mass Index on Coordination, Static and Dynamic Balance in Young Adults: A Case-control Study - Ankita Debnath; Manish Kumar; Mamta Dagar; Vishwajeet Trivedi; Ashish Tyagi; AS Moorthy (Journal of Clinical and Diagnostic Research)
Introduction: Abnormal Body Mass Index (BMI), characterised by a higher percentage of fat mass, has notable effects on postural control, leading to a forward shift in posture that exceeds the Base Of Support (BOS) boundary due to increased segmental mass and a compromised ability to regain stability after a disruption caused by excess adiposity.